Online work from bali selama pandemi covid-19: model pemasaran daerah tujuan wisata - Jenita; Asep Saepudin; Lucky Radi Rinandiyana; Tine Badriatin; Ramon Arthur Ferry Tumiwa (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
The government formed the Work From Bali (WFB) initiative aimed at State Civil Apparatus (ASN) to help the tourism sector on the Island of the Gods to revive due to the Covid-19 pandemic. The government has decided to hold the Work From Bali (WFB) program in the Nusa Dua area of ​​Bali. The Nusa Dua area of ​​Bali is managed by a State-Owned Enterprise (BUMN), in particular the Indonesian Tourism Development Agency. This study aims to uncover the discourse on Work From Bali (WFB) news in the midst of the Covid-19 pandemic. The method used in this research is critical discourse analysis by van Dijk. The unit of analysis of this research is Kompas.com online news related to Work From Bali (WFB) in the midst of the Covid-19 pandemic in the period 27 May 2021 to 31 May 2021. The results show that the news discourse that appears related to Work From Bali (WFB) in In the midst of the Covid-19 pandemic, there is an economic discourse in boosting tourism in Bali. However, these efforts still require re-examination so that social considerations do not arise that focus on activities that must be carried out in Bali.